PENGEMBANGAN MODUL TEKNIK BUDIDAYA TANAMAN KEDELAI SEBAGAI BAHAN AJAR SEKOLAH MENENGAH KEJURUAN - Maria Monicha Faot; Siti Zubaidah; Heru Kuswantoro (Graduate School of Universitas Negeri Malang, 2016)
Modules are printed instructional materials were studied independently by students to achieve the expected competencies. The module was developed based on research by the authors of the correlation and path analysis of agronomic characters some promising lines resistant soy CpMMV (cowpea mild mottle virus). This study aims to produce modules soybean crop cultivation techniques as teaching material vocational students. Module development using the 4D model Thiagarajan. Results matter expert validation criteria of 79,55% with